Assessing the potential impact on poverty of rising cereals prices : the case of Ghana - Wodon, Quentin, 1963- 1963- (Policy research working paper, 2008)
"Concerns have been raised about the impact of rising food prices worldwide on the poor. To assess the (short term) impact of rising food prices in any particular country it is necessary to look at both the impact on food producers (who benefit from an increase in prices) and food consumers (who loose out when the price increases), with a focus on poor producers and consumers. In Ghana, the impact of a change in the price of rice is not ambiguous because a large share of the rice consumed is imported, so that the negative impact for consumers is much larger than the positive impact for producers. For maize by contrast, the impact is ambiguous since much of the consumption is locally produced. Using a recent and comprehensive household survey, this paper provides an assessment of the potential impact of higher food prices on the poor in Ghana using both simple statistical analysis and non-parametric methods. The paper finds that rising food prices for rice, maize, and other cereals would together lead to an increase in poverty, but that by contrast to a number of other countries, this increase, while not negligible, may not be as large as feared. "--World Bank web site